Microwave Absorbers Development For Anechoic - Mohd Ibrahim, Imran (2007)
The most important element in an anechoic chamber is absorbers. Absorbers will absorb an electromagnetic wave to provide nonreflecting environments similar to outer space. Absorbers have been developed at Microwave Laboratory, Faculty of Electronic and Computer Engineering, UTeM, consisting of absorbing material in pyramid shape, carbon powder and coating liquid (paint). Absorbers are coated with carbon using oil and water-based paint. This paper highlights the design and construction of the absorbers, as well as the measurement system configuration for absorption measurements. The result is compared with those of commercially available absorbers.